REVITALIZATION OF WATER RESOURCES LAW ENFORCEMENT: THE ROLE OF LOCAL WISDOM AND PARTICIPATION OF KOTABARU INDIGENOUS COMMUNITIES IN LEGAL ETHNOGRAPHY - Trisna Agus Brata; Abdul Halim Barkatullah; Imam Syafa’i (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Indonesia is facing a water resources (SDA) management crisis marked by a moderate Water Quality Index (IKA) and 112 drought-prone areas, exacerbated by environmental degradation and ineffective law enforcement of Law No. 17/2019 concerning Water Resources, 70% of cases are only resolved administratively). This study aims to identify the principles of Huma Betang in water law enforcement in Kotabaru, analyze the effectiveness of indigenous communities as law enforcement agents, and develop an ethnography-based adaptive revitalization model. The method uses a legal ethnography approach with in-depth interviews, participatory observation, and legal document analysis, analyzed thematically with triangulation. The findings show that the principles of Huma Betang (Ulayat Water Rights, Gawi Manuntung Waja, Belom Bahadat) reduce minor violations and resolve water disputes at the customary level, although they are hampered by integration with state law. The "Straight Path" model is proposed as an integrative solution through the Customary-State Consultation Forum, Integrated Reporting System, Certification of Water Caretakers, and Tiered Sanctions. Theoretically, the research enriches ecolegal pluralism with the mechanism of "living law"; practically, it provides a blueprint for revitalization. In conclusion, revitalization requires engineering institutional interactions that accommodate local wisdom, with implications for the revision of Law No. 17/2019, hybrid certification, and integrated escalation protocols. Further research suggestions include model replication tests in other indigenous communities and studies on the transformation of gender roles post-digitalization.